Nitrogen abundances of the Be-type stars in 30 Doradus - Dufton, Philip L.; Langer, N.; Lennon, D. J.; Schneider, Fabian; Evans, C. J.; Sana, H.; Taylor, W. D. (Monthly notices of the Royal Astronomical Society, 2024)
A sub-set of the 67 Be-type stars observed in 30 Doradus during the VLT-FLAMES Tarantula Survey (VFTS) campaign have been analysed to estimate atmospheric parameters and chemical compositions, in particular their nitrogen abundance. Reliable results were found for 23 targets comprising the largest Large Magellanic Cloud sample currently available. The nitrogen abundance estimates have been compared with predictions from evolutionary models for rapidly rotating single stars (or non-interacting multiple systems) and for interacting binaries. The observations appear to be incompatible with all the targets having a single star evolutionary history. The results agree better with a binary evolutionary history with at least 30 per cent of the VFTS sample having apparently evolved by this pathway. These conclusions are consistent with a previous analysis of the v(e) sin i-estimates for this Be-type sample.
Gesehen am 30.09.2024